A study of clinical profile, pulmonary function tests, arterial blood gas analysis and echocardiography in patients with chronic cor pulmonale. - Paudel, Vijaya Prasad (1999)
ABSTRACT: Forty-two patients of chronic cor pulmonale were studied clinically and by chest x-ray electrocardiography, pulmonary function tests, arterial blood gas analysis and echocardiography. Pulmonary arterial pressure was calculated by triscuspid regurgitation jet by Doppler echocardiography using modified Bernoulli equation . Correlation was performed between pulmonary arterial pressure and parameters of pulmonary function tests and arterial blood gas analysis. Forty-six patients (34female and 12 male ) were initially selected for study. All patients had cough with or without expectoration and varying degree of breathlessness (100%). Thirty-nine patients (92.9%) had bilateral pitting oedema of legs. Thirty-two (76.2%) patients had cardiomegaly on chest radiography. Electrocardiographic study showed: right axis deviation in 34 (81%) patients , R/S ratio in VI morethan 1 in 21 (50%) and qR in V1 in 17 (40.5%) patients . Pulmonary function tests were performed in 42 cases (100%) . Obstructive type of ventilator defect was present in 40 cases (95.2%) and restrictive type of ventilator defect in 2 cases(4.8%). The mean FEVI was 0.44 L+_0.13 and mean FVC was 1.035 L+_0.85 Arterial blood gas analysis was done in 34 cases (80.9%) . The mean arterial oxygen tension PaO2was 42.79+_8088 mean PaCO2was 52.6+_13 and mean pH 7.40+_0.053. Echocardiography of the 42 haemodynamically stable patients were studied. The mean Pulmonary artery pressure measured was 74.9 mmHg +_ 18.63. Two patients (4.8%) had normal resting pulmonary arterial pressure and 38 (90.4%) patients had pulmonary arterial pressure of more than 50mm Hg . The thickness of the anterior right ventricular wall in systole was 10.88 mm +_ 1.67 whereas in diastole 8.45 mm +_ 1.51. Mean RIVD was 28.8 +_ 4.90 and RIVD mm was 33.92 +_6.32. There was correlation between mean FVC and mean PaO2 and between mean FVC and pa CO2 (p<0.05). FEVI and smoking were not correlated. There was also no correlation between mean PAP and mean FVC. Similarly, mean FEVI 1 and mean paO2 were not correlated, neither was mean PAP and mean O2 saturation percentage. In conclusion clinical , radiological , electrocardiographic and other non- invasive methods are helpful for diagnosis of chronic cor pulmonale. The echocardiography was found to be most useful and reliable method to assess and quantify the morphologic changes of right heart in chronic cor pulmonale with pulmonary hypertension and also to measure pulmonary arterial pressure.